Learning assessment during COVID-19: A case study of six Moroccan institutions - Kodad, Salma; Kaaouachi, Abdelali (Edelweiss Applied Science and Technology, 2026)
The global impact of the COVID-19 pandemic affected Morocco's education sector, prompting a rapid shift to online learning in higher education. This study presents a case analysis based on a survey of the mode of learning assessment adopted by Moroccan universities during the pandemic. Participants included university officials and researchers interested in distance education from six Moroccan higher education institutions. The analysis examines in detail the Moroccan experience regarding the integration of technology into learning assessment during the pandemic, emphasizing organizational, pedagogical, technical, ethical, and emotional aspects of this transition. The findings reveal significant challenges, such as maintaining exam integrity and adapting to digital tools. The study concludes that sustainable progress in this area depends on teacher training, improved digital infrastructure, and the development of strong ethical frameworks for online assessment. These insights contribute to a better understanding of the resilience of the Moroccan higher education system and offer practical recommendations for stakeholders and academic leaders aiming to improve assessment practices in blended and fully online environments.